ANALISIS KOORDINASI DAN KOMUNIKASI DALAM IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH - Anak Agung Gede Agung; Chindytia; Ni Putu Devi Wedayanti; Melly Cahyani, Putu; Ni Luh Putu Wirasanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze coordination and communication in the implementation of School-Based Management (SBM) at SD Negeri 5 Ketewel. Coordination and communication are important factors in supporting the effectiveness of school management because they influence collaboration, decision-making, and the implementation of school programs. This study used a qualitative approach with a descriptive research design. Data were collected through observation, interviews, documentation, and literature studies involving the principal, teachers, and educational staff. The results showed that coordination in the implementation of SBM had been carried out through clear task distribution, routine meetings, participatory program planning, and periodic monitoring and evaluation activities. Communication among school stakeholders was also conducted openly and participatively through deliberation, direct information sharing, and the use of digital communication media such as WhatsApp groups. These coordination and communication practices supported the effectiveness of school programs and created harmonious cooperation among school members. However, communication and coordination with external stakeholders, especially parents, were still not optimal and need further improvement. Overall, effective coordination and communication play an important role in supporting the successful implementation of School-Based Management at SD Negeri 5 Ketewel.